Regulacje prawne w 6. i 7. Programie Ramowym Unii Europejskiej - podobieństwa i różnice - Wasylkowska, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The article raises the issue of the 6th and 7th UE Framework Programme’s legal regulation. The question it tries to answer is how such regulations work in practice. The article is divided into two main parts. The first one introduces the legal regulations which can be met in projects which are performed under the 6th UE Framework Programme and the second one presents a summary of legal regulations which can be met in 7th UE Framework Programme’s projects. In both cases these legal regulations are mainly connected with financial issues. In both parts the author firstly mentions the types of projects, then she focuses on the way in which the European Community contributes to the projects and what are the types of costs. In the first part the types of costs are described in detail. The author emphasises the differences between eligible and non-eligible as well as direct and indirect costs. Describing the eligible costs the author focuses on the personnel costs and the legal form of agreements which are concluded with people who are working on the projects realised in Poland.
Keywords: projekt; Unia Europejska; finansowanie; programy unijne